Prolyl-hydroxylase inhibition preserves endothelial cell function in a rat model of vascular ischemia reperfusion injury - Barnucz, Enikő; Veres, Gábor; Hegedűs, Péter; Klein, Stephanie; Zöller, Raphael; Radovits, Tamás; Korkmaz-İçöz, Sevil; Horkay, Ferenc; Merkely, Béla; Karck, Matthias; Szabó, Gábor (The journal of pharmacology and experimental therapeutics, 2013)
Storage protocols of vascular grafts need further improvement against ischemia-reperfusion (IR) injury. Hypoxia elicits a variety of complex cellular responses by altering the activity of many signaling pathways, such as the oxygen-dependent prolyl-hyroxylase domain-containing enzyme (PHD). Reduction of PHD activity during hypoxia leads to stabilization and accumulation of hypoxia inducible factor (HIF) 1α. We examined the effects of PHD inhibiton by dimethyloxalylglycine on the vasomotor responses of isolated rat aorta and aortic vascular smooth muscle cells (VSMCs) in a model of cold ischemia/warm reperfusion. Aortic segments underwent 24 hours of cold ischemic preservation in saline or DMOG (dimethyloxalylglycine)-supplemented saline solution. We investigated endothelium-dependent and -independent vasorelaxations. To simulate IR injury, hypochlorite (NaOCl) was added during warm reperfusion. VSMCs were incubated in NaCl or DMOG solution at 4°C for 24 hours after the medium was changed for a supplied standard medium at 37°C for 6 hours. Apoptosis was assessed using the TUNEL method. Gene expression analysis was performed using quantitative real-time polymerase chain reaction. Cold ischemic preservation and NaOCl induced severe endothelial dysfunction, which was significantly improved by DMOG supplementation (maximal relaxation of aortic segments to acetylcholine: control 95% ± 1% versus NaOCl 44% ± 4% versus DMOG 68% ± 5%). Number of TUNEL-positive cell nuclei was significantly higher in the NaOCl group, and DMOG treatment significantly decreased apoptosis. Inducible heme-oxygenase 1 mRNA expressions were significantly higher in the DMOG group. Pharmacological modulation of oxygen sensing system by DMOG in an in vitro model of vascular IR effectively preserved endothelial function. Inhibition of PHDs could therefore be a new therapeutic avenue for protecting endothelium and vascular muscle cells against IR injury.